0128 Maternal Sleep Quality Across Pregnancy Predicts Newborn Neurodevelopment. (25th May 2022) - Nevarez-Brewster, Melissa; Demers, Catherine; Mejia, Alexandra; Hasse, Mercedes Hoeflich; Styner, Martin; Bagonis, Maria; Kim, SunHyung; Gilmore, John; Hoffman, M; Hankin, Benjamin; Davis, Elysia
Abstract: Introduction: The prenatal period is characterized by immense fetal neuronal growth. Such rapid growth can increase fetal susceptibility to prenatal environmental insults (Barker, 1998). A promising prenatal process that may alter fetal development is maternal prenatal sleep quality. Poor prenatal sleep quality is a public health concern affecting approximately 78% of pregnant individuals (Lucena et al., 2018). In rodents, maternal sleep deprivation across gestation predicts offspring hippocampal neurogenesis, with pups exposed to sleep deprivation early and late in pregnancy exhibiting more anxiety and depression-like behaviors (Peng et al., 2015). In humans, poor sleep quality in other developmental stages predicts hippocampi and amygdalae changes (Marshall & Born, 2007; Saghir et al., 2018). However, the relation between prenatal sleep quality and offspring brain development in humans remains poorly understood. The present study examined associations between maternal sleep quality in early, mid, and late pregnancy, and newborn hippocampal and amygdala volume, regions implicated in memory and emotion. Methods: Pregnant individuals (N=94; Mage=30.5; SDage=5.3) reported on sleep quality three times during pregnancy. Newborn (Mageinweeks=5.1; SDageinweeks=2.7) hippocampi and amygdalae volumes were assessed during an unsedated sleep cycle using magnetic resonance imaging (MRI). Tissue segmentation was collected using a multiatlas iterative algorithm that individually segmented the regions of interest and subsequently combined T1- and T2-weighted high-resolution images (See neonate multiatlas at https://www.nitrc.org/projects/unc_brain_atlas/ ). Bivariate correlations examined the association between prenatal sleep quality and hippocampus and amygdala volume. Partial correlations examined these associations in the presence of significant cofounding variables including intracranial volume, body weight percentile, sex, and postconceptional age. Results: Partial correlations revealed that poor maternal sleep quality early in pregnancy predicted larger newborn bilateral hippocampal volume (all rs<.25; ps<.038). Associations with sleep later in gestation persisted for the right hippocampus (all rs<.25; ps<.038). Prenatal maternal sleep quality did not significantly predict newborn amygdala volume (all rs<-.06; ps>.58). Conclusion: This study provides novel evidence linking prenatal sleep quality and newborn hippocampal volume in humans, suggesting the presence of an intergenerational link between prenatal sleep health and offspring well-being. Support (If Any): Support (if any): NIMH R01MH109662, NHLBI R01HL155744, and diversity training supplement for 1st author; F32MH125572 for 2nd author.